Aspectos ecológicos da avifauna aquática nas fozes dos rios Tijucas e Inferninho, Santa Catarina, Brasil - Rubert, Barbara (2016)
Estuaries are highly productive environments susceptible to environmental variables, and important to the life cycle of various species, to waterfowl serve as a point of rest, feeding and nesting. These sites also receive migratory birds seeking the accumulation of energy required for the return to the reproductive areas. These species, as well as residents, have their distribution, occurrence, abundance and behavior influenced by environmental variables, seasonality and human presence. Thus this study aimed to characterize the structure of the community of waterfowl, as well as behavioral pattern, relationship with environmental variables and habitat use by them in the mouths of the rivers Tijucas and Inferninho. The Tijucas’ Bay where this study was conducted, presents sediment deposition and formation of extensive muddy plans. To collect the data length of 1.1 km was covered in each mouth, from June 2015 to May 2016, sampling occurred every two hours, from 08 hours to 16 hours. The data collected were species, average number, activity and micro-habitat. five microhabitats were considered, based on different faces found in two locations, and analyzed environmental variables were: wind speed, tide height, precipitation and temperature. The curve of rarefaction and Jackknife 2 were used to determine the sample sufficiency, Shannon index was used to estimate the annual and monthly diversity and similarity among the studied areas was calculated using the Jaccard index. Analysis of Variance (ANOVA) and Kruskal-Wallis test were used to determine the differences between species richness, average number and behavior of the species for hours and months of sampling. The behavior relative frequency was grouped by similarity of Bray-Curtis, the Indicator Species Analysis was used to determine the association of species with micro-habitats, and used Canonical Correlation Analysis (CCA) to determine the correlation between the variables environmental and behavior and between species. Were recorded 44 species of waterfowl in the voices of the two rivers, 10 migratory. The similarity between the two areas was 75%, indicating high similarity of microhabitats between areas. The diversity at the mouth of the river Tijucas was higher than the mouth of the river Inferninho, this difference is related to river discharge of rivers, hence the nutrient input. The difference in species richness, abundance was significant only between the months of observation, and the months with the highest diversity occurred in the late spring, summer and early fall, probably due to the life cycle and arrival of migratory species. The rest was the most frequent activity, followed by foraging, this was negatively related to temperature variation, it suggests that the higher the temperature, the lower the foraging, avoiding waste of energy and water. Foraging was negatively correlated with the height of the tide as the low tide provides a food resource. The indicator species analysis showed that most of the species was associated with only one micro-habitats, this can be explained by the abundance of available resource, since rich environments allow specialization of species.